Perceived School Climate Support Moderates the Relationship Between Teachers’ Growth Mindset and Work Engagement - Kai Zhang; Wu-Jing He (Education Sciences)
This study examines how perceived school climate support moderates the relationship between teachers’ growth mindset and work engagement. A sample of 353 teachers (56% females) from Shanghai City, China, completed the Growth Mindset Inventory (GMI) and the Utrecht Work Engagement Scale (UWES) to evaluate their growth mindset and work engagement levels, respectively. The School Environment Scale (SES) was used to measure perceived school climate support across five dimensions: collaboration, student relations, decision-making, instructional innovation and school resources. Hierarchical regression analyses were employed to examine the moderating effects of each dimension of perceived school climate support on the relationship between a growth mindset and work engagement. The results indicated that (1) a growth mindset was a positive predictor of work engagement, suggesting that teachers who view their abilities as developable are more engaged in their professional roles, and that (2) all five dimensions of perceived school climate support significantly and positively moderated this relationship, suggesting that perceived school climate support enhances the impact of a growth mindset on work engagement. These findings underscore the importance of targeted environmental factors in maximizing the benefits of growth mindset interventions among teachers, thereby providing actionable insights for educational leaders to improve teacher engagement through focused climate enhancements.